Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Survival of Eurasian lynx in the human‐dominated landscape of Europe - J. Premier; M. L. Bastianelli; J. Oeser; O. Anders; H. Andren; M. Aronsson; G. Bagrade; E. Belotti; C. Breitenmoser‐Würsten; L. Bufka; R. Černe; J. Červený; et al. (Conservation Biology, 2025)
Survival and cause‐specific mortality rates are vital for evidence‐based population forecasting and conservation, particularly for large carnivores, whose populations are often vulnerable to human‐caused mortalities. It is therefore important to know the relationship between anthropogenic and natural mortality causes to evaluate whether they are additive or compensatory. Further, the relation between survival and environmental covariates could reveal whether specific landscape characteristics influence demographic performance. We used telemetry data on 681 Eurasian lynx ( Lynx lynx ), a model apex predator with large spatial requirements, that were tracked across their European distribution. Through time‐to‐event analyses, we sought to determine the variables associated with differences in their survival. Illegal killing was the main cause of mortality (33.8%), and mortality rates were similar in protected and hunted populations (8.6% and 7.0% per year, respectively). Survival varied greatly across populations (70–95% per year). Across all study sites, higher hunting and anthropogenic mortality rates were partially compensated by lower rates of other mortality causes but not by natural mortality alone. Variation in survival depended on sex (female survival was 1.5 times greater than male survival) and seasonality (highest risk during hunting season and winter), and lower survival rates were correlated with higher human modification of landscapes at both coarse (home range composition) and fine (habitat use within home range) scales. Some variation in survival was driven by unobserved factors, which, given the high rates of human‐caused mortalities, including illegal killing, are of foremost concern. Due to the low natural mortality rates in protected and hunted populations, we conclude that anthropogenic causes of mortality are likely close to additive, such that maintaining or increasing refuge habitat with little human disturbance is critical to lynx conservation.

Long-term exposure to traffic noise and risk of incident colon cancer: A pooled study of eleven Nordic cohorts - Nina Roswall; Jesse D. Thacher; Mikael Ögren; Andrei Pyko; Agneta Åkesson; Anna Oudin; Anne Tjønneland; Annika Rosengren; Aslak H. Poulsen; Charlotta Eriksson; David Segersson; Debora Rizzuto; et al. (Environmental Research, 2023)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

The spatial variation of O3, NO, NO2 and NO x and the relation between them in two Swedish cities - Annika Hagenbjörk; E. Malmqvist; K. Mattisson; Nilsson J. Sommar; L. Modig (Environmental Monitoring and Assessment, 2017)